Do gênero provérbio ao verbete: uma produção interacionista sócio-discursiva na educação de jovens e adultos - Matias, Ana Lídia Freire (2014)
This paper presents a reflection on the importance of using text genres in the teaching of young people and adults, with a supported approach in the socio-discursive interactionism. The option to use the saying gender was due to the importance of valuing popular culture as a way to build and improve in new knowledge, as Paulo Freire believed. We had intended to add one more reflection on teaching practice in adult education (Youth and Adult Education). This paper presents the results of a qualitative-interpretative character of action research that aims to present reflections on the possible contributions of ISD, from the didactic sequence proposed. With this observation applied and interventionist nature, promote the exploitation of our students, in the sense that they can act as producers of relevant texts, from a teaching proposal that considers the situational context of oral saying genre and enhances the textual production and their linguistic and discursive features, through writing and rewriting. The survey was conducted in the cycle II of AYE, at the Municipal School Major José de Barros Moreira, in the city of João Pessoa, PB. The methodological procedures used involved participant observation with audio recording and records the activities of students through a teaching sequence (DOLZ; SCHNEUWLY, 2004). The corpus consists of the transcript of the recording a few classes, where students discussed some popular sayings and the textual productions of the students. The analysis occurred after observation in the classroom, through audio discussion with students about proverbs and written productions. Thus, these results were compared with our theoretical framework and it was identified that the written productions can be beneficial from the world of reading that students undertake in their daily lives. The results of this work were the reading and interpretation of proverbs, entries production and a book prepared by the students, to support these entries. It was observed that the writing activities and rewriting of entries resulted in the development of language skills.